FEATURES OF VOLLEYBALL LESSONS IN PHYSICAL EDUCATION - Abatova Gulzar Nurlanovna (PEDAGOGS, 2024)
Abstract: Volleyball is one of the most effective health-improving educational means that have a complex positive effect on the body of those who practice this sport. In line with the concept of physical education in schools, the main attention is paid to improving the quality of classes, various physical education and sports events in terms of introducing effective technologies based on a personality-oriented approach, differentiated and individual learning. Volleyball classes satisfy various physical education and wellness interests, as well as the requirements of the physical education program.